(3EOGQI GdTQGA hGdJNRjf (B:s (3eONd cej (B/s - (3Rhjda, egOj MSfs; (3GdYdGhfI, Ydj Sdje s ((3YeGf(B: s (3OGQ CLfGOjf ddfTQ(B, s, 2007)
(3CSGSjGJ GdTQGA(B- (3GdCUhd GdYdejI ddTQGA(B- (3JNWjW fTGW EOGQI GdTQGA(B- (3Jbjje fTGW EOGQI GdTQGA(B-(3EOGQI GdJNRjfs
Keywords: (3GdJNRjfs; (3GdJNWjWs; (3GdTQGAs